2018
DOI: 10.1016/j.acclit.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and consequences of executive compensation-related shareholder activism and say-on-pay votes: A literature review and research agenda

Abstract: This systematic literature review analyses the determinants and consequences of executive compensation-related shareholder activism and say-on-pay (SOP) votes. The review covers 71 empirical articles published between January 1995 and September 2017. The studies are reviewed within an empirical research framework that separates the reasons for shareholder activism and SOP voting dissent as input factor on the one hand and the consequences of shareholder pressure as output factor on the other. This procedure id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 127 publications
2
52
0
Order By: Relevance
“…This voting approach is known as the "say-on-pay," a tool which can be used by shareholders to express dissent about the recommendations made in remuneration reports (Mallin, 2016;Mangen & Magnan, 2012). Since then, many research studies have investigated the antecedents and the consequences of say-on-pay voting (for recent reviews, see Stathopoulos & Voulgaris, 2015;Obermann & Velte, 2018). Among some of these antecedents that most affect shareholder dissent via say-on-pay voting are higher CEO remuneration, firm performance and firm size, and weak boardroom governance (Alissa, 2015;Conyon, 2016;Conyon & Sadler, 2010;Ferri & Maber, 2013;Gregory-Smith, Thompson, & Wright, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This voting approach is known as the "say-on-pay," a tool which can be used by shareholders to express dissent about the recommendations made in remuneration reports (Mallin, 2016;Mangen & Magnan, 2012). Since then, many research studies have investigated the antecedents and the consequences of say-on-pay voting (for recent reviews, see Stathopoulos & Voulgaris, 2015;Obermann & Velte, 2018). Among some of these antecedents that most affect shareholder dissent via say-on-pay voting are higher CEO remuneration, firm performance and firm size, and weak boardroom governance (Alissa, 2015;Conyon, 2016;Conyon & Sadler, 2010;Ferri & Maber, 2013;Gregory-Smith, Thompson, & Wright, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus on the effect of women on the remuneration committee as previous studies have shown women are more likely to be effective monitors (Adams & Ferreira, 2009;Carter, Simkins, & Simpson, 2003), more ethical (Cumming, Leung, & Rui, 2015), and more likely to reduce information asymmetry (Abad, Lucas-Pérez, Minguez-Vera, & Yagüe, 2017;Srinidhi, Gul, & Tsui, 2011). In addition, there are presently limited studies on the effect of women on the remuneration committee (Kirsch, 2017;Obermann & Velte, 2018). Scholars have called for additional studies on the role of women on the remuneration committee and then on executive remuneration, including CEO pay with the aim to understand if they help to avoid suboptimal pay, and hence reduce shareholders' dissent (Filatotchev & Wright, 2017;Kirsch, 2017;Strobl, Rama, & Mishra, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second step, and as in other related literature reviews (Obermann & Velte, 2018), the keywords are applied to five major academic journal databases -ISI Web of Science, ScienceDirect, SAGE Journals, Emerald Insight, and Wiley Online Library, Google Scholar. For the field of business economics, only peer-reviewed journal articles in the English language were considered.…”
Section: Data Selectionmentioning
confidence: 99%
“…Given the current relevance of the topic, the following paper synthesizes and discusses empirical research on the impact of IO on ESG and vice versa, as also other ownership types (e.g., managerial ownership) and other stakeholder groups (e.g., customers, suppliers, employees) can foster the ESG activities of a firm. Given the dominance of empirical research on institutional investors (Obermann & Velte, 2018) and its huge power, IO's concentration is justified in this literature review. Therefore, empirical-quantitative (archival) articles are included that analyze 1) the impact of IO on ESG performance and disclosure, 2) the impact of ESG performance and disclosure on IO as a bi-directional relationship, and 3) the moderating and mediating influence of IO on the firms' financial consequences of ESG.…”
Section: Introductionmentioning
confidence: 99%